2019
DOI: 10.3390/foods8110537
|View full text |Cite
|
Sign up to set email alerts
|

Swordfish or Shark Slice? A Rapid Response by COIBar–RFLP

Abstract: Market transparency is in strong demand by consumers, and the authentication of species is an important step for seafood traceability. In this study, a simple molecular strategy, COIBar–RFLP (cytochrome oxidase I barcode–restriction fragment length polymorphism), is proposed to unveil commercial fraud based on the practice of species substitution in the swordfish trade. In particular, COI barcoding allowed the identification of the species Prionace glauca, Mustelus mustelus, and Oxynotus centrina in slices lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 65 publications
1
17
0
1
Order By: Relevance
“…The recent sequencing revolution has allowed researchers to go to even greater depths with regard to seafood traceability [55], with genomic tools allowing not only the species, but also population to be identified [56][57][58]. Although such new technology has much to offer, our results and recent studies published using PCR-RFLP for traceability in other seafood products [59][60][61][62][63] underline the continued use of PCR-RFLP as a cost-effective, fast, and simple means to identify salmonid species and mislabeling at the point of sale.…”
Section: Discussionmentioning
confidence: 74%
“…The recent sequencing revolution has allowed researchers to go to even greater depths with regard to seafood traceability [55], with genomic tools allowing not only the species, but also population to be identified [56][57][58]. Although such new technology has much to offer, our results and recent studies published using PCR-RFLP for traceability in other seafood products [59][60][61][62][63] underline the continued use of PCR-RFLP as a cost-effective, fast, and simple means to identify salmonid species and mislabeling at the point of sale.…”
Section: Discussionmentioning
confidence: 74%
“…El método de reacción en cadena de la polimerasapolimorfismos de longitud de fragmentos de restricción (PCR-RFLP, por sus siglas en inglés) permite la identificación de especies basada en los productos de la digestión del ADN mediante el empleo de enzimas de restricción (Guan et al 2018). Este método tiene la ventaja de ser rápido, sencillo, robusto y relativamente más barato que la secuenciación, y ha sido aplicado para diferentes propósitos, por ejemplo, para la identificación de organismos en estado larval o para la trazabilidad de alimentos marinos (García-Rodríguez et al 2008, Ferrito et al 2019. Recientemente, los procedimientos de PCR-RFLP se han incorporado a nuevos enfoques para detectar especies acuáticas basadas en el ADN ambiental (Clusa et al 2017, Fernández-Fernández 2018.…”
Section: Sampling and Dna Extractionunclassified
“…The polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method allows the identification of species based on products created by DNA digestion using restriction enzymes (Guan et al 2018). This method has the advantage of being fast, simple, robust, and relatively cheaper than the sequencing method, and it has been applied for different purposes, for example, for the identification of organisms in the larval stage or for seafood traceability (García-Rodríguez et al 2008, Ferrito et al 2019. Recently, PCR-RFLP procedures have been incorporated into new approaches for detecting aquatic species based on environmental DNA (Clusa et al 2017, Fernández-Fernández 2018.…”
mentioning
confidence: 99%
“…In this regard, this Special Issue aimed at gathering original research and review papers focusing on the development and application of both targeted and non-targeted methodologies to verify food authenticity and traceability. This Special Issue includes eighteen notable contributions, comprising one review paper and seventeen original research papers, these last dealing with the authentication of different foods, including some considered as highly prone to food fraud such as olive oil [ 14 , 15 ], honey [ 16 , 17 ], fish [ 18 , 19 , 20 ] and meat [ 21 , 22 , 23 , 24 ].…”
mentioning
confidence: 99%
“…The proposed normalized real-time PCR system, which required the amplification of the specific target ( G. biloba ITS1 region) using the novel primer set and TaqMan probe and a reference endogenous gene (nuclear 18S rRNA), exhibited high performance parameters and was successfully validated using blind mixtures. To assess the occurrence of fraud in the swordfish supply chain, Ferrito et al [ 20 ] suggested the use of a different molecular strategy encompassing the PCR amplification of the frequently used barcode COI gene combined with the restriction fragment length polymorphism (RFLP) technique. The COIBar-RFLP procedure was applied on several authenticated reference samples of swordfish ( Xiphias gladius ) and four different shark species to generate species-specific restriction enzyme patterns.…”
mentioning
confidence: 99%